Multi Aspect Optimization of Milling Machines : Review - Firmansyah, Mohamad Ardy; Pranoto, Hadi (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
Modern manufacturing supports various aspects of modern life. Modern manufacturing right now is focused on the application of artificial intelligence, acceleration of production, automation production, sustainability and environmental protection. A milling machine is a tool supports in a series of production processes. Its existence supports the production process which is part of the modern manufacturing system. In operating milling machines, several problems that occur, starting from operations, machine capacity, and predictions of machine or tool usage. This study summarizes and reviews previous studies in order to collecting types of milling machine optimization. Multi-aspect optimization obtained includes: optimization with a tool life prediction approach, optimization with a milling process approach, optimization with modification or retrofit, optimization with a production yield approach and finally optimization with operational time. With the results obtained, it is hoped that it can contribute to the optimization of milling machines in the modern manufacturing world. It is hoped that future research will be able to carry out in-depth analysis of each aspect of milling machine optimization has been mentioned.